Tape-assisted reciprocal teaching: Cognitive bootstrapping for poor decoders - Le Fevre, Deidre M.; Moore, Dennis W.; Wilkinson, Ian A. G. (British journal of educational psychology, 2003)
Background: Students who have limited skills in decoding and comprehension and who lack motivation to read present difficulties for practitioners. Difficulties may be compounded when these students lack access to age‐appropriate and interesting text and have lost the notion of reading as a process of obtaining meaning from print. Aims: This research examined the effects of a modified reciprocal teaching intervention for readers with poor decoding skills and poor comprehension. Tapeassisted reciprocal teaching was used to help students with poor decoding skills develop cognitive and metacognitive strategies and improve their comprehension of high interest expository texts. Methods: Two single‐subject research design studies involving four groups of students were conducted. Study I involved one experimental group and Study II was a multiple baseline design involving three experimental groups. Sample: Each experimental group comprised a heterogeneous mix of six students, three with poor decoding skills and three with adequate decoding skills, all of whom showed poor comprehension. Results: As a result of the tape‐assisted reciprocal teaching, the poor decoders demonstrated improved application of cognitive and metacognitive strategies and improved comprehension. These improvements were shown on both researcherdeveloped and standardised tests as well as on maintenance and transfer measures. The students with adequate decoding skills also showed improvements in comprehension. Conclusions: The success of the intervention for poor decoders suggests that tape assisted reciprocal teaching may be seen as a form of ‘cognitive bootstrapping’ to enable poor readers to escape the cycle of reading failure and engage more meaningfully in the process of reading.